Higgs Phenomenology of Minimal Universal Extra Dimensions - Kakizaki Mitsuru; Brown Matthew; Belyaev Alexander; Bélanger Geneviève; Pukhov Alexander (EPJ Web of Conferences, 2012)
The minimal model of Universal Extra Dimensions (MUED) is briefly reviewed. We explain how the cross-sections for Higgs production via gluon fusion and decay into photons are modified, relative the the Standard Model (SM) values, by KK particles running in loops, leading to an enhancement of the gg → h → γγ and gg → h → W+W− cross-sections. ATLAS and CMS searches for the SM Higgs in these channels are reinterpreted in the context of MUED and used to place new limits on the MUED parameter space. Only a small region of between 1 and 3 GeV around mh = 125 GeV for 500 GeV < R−1 < 1600 GeV remains open at the 95 % confidence level.